Analisis Faktor Hipertensi, Diabetes Mellitus Dan Infeksi Saluran Kemih Terhadap Tingkat Keparahan Gagal Ginjal Kronik Pada Pasien Yang Menjalani Hemodialisa - Rifaldi, Ibnu; Hamzah, Hamzah; Harun, Lukman (Bunda Edu-Midwifery Journal (BEMJ), 2024)
Chronic kidney disease (CKD) is a world health problem with increasing incidence, prevalence morbidity, and mortality rates with the 20th highest mortality rate in the world. Several causal factors can increase the severity of chronic kidney failure in patients undergoing hemodialysis, resulting in permanent damage to kidney function, namely hypertension, diabetes mellitus, and urinary tract infections.This study aims to analyze the factors of hypertension, diabetes mellitus, and urinary tract infections on the severity of chronic kidney failure in patients undergoing hemodialysis at the Banjarmasin Islamic Hospital.This research is an observational analytical correlation with a cross-sectional approach carried out one time at a time with a population of 567 respondents. The research instrument used a documentation sheet to collect data on respondents, obtaining a sample of 216. The sampling technique used was purposive sampling by determining the samples to be taken according to the inclusion and exclusion criteria. Bivariate analysis uses Chi-square and multivariate analysis uses logistic regression.The results showed that the factors of hypertension and diabetes with the severity of CKD have a p-value of 0.006 and 0.011. Where, there is a relationship between hypertension and DM factors. The results of the multivariate analysis show that the independent variable that is most related to the severity of chronic kidney failure is the hypertension variable with a p-value of 0.007 with exp(B) 432. Hypertension and diabetes mellitus are factors that can increase the severity of chronic kidney failure